Harvesting feminist knowledge for public policy rebuilding progress - Devaki Jain,Ed; Elson, Diane, Ed (Sage Publications, 2011)
Reflecting on the flaws in the patterns of development, this title argues for political, economic, and social changes to promote equality and sustainability. It also argues that the very approach being taken to understand and measure progress, and plan for and evaluate development, needs rethinking in ways that draw on the experiences of women.